GPS-Geodetic Deformation Monitoring of the South-west Seismic Zone of Western Australia: Review, Description of Methodology and Results from Epoch-one - Featherstone, Will; Penna, N.; Leonard, M.; Clark, D.; Dawson, J.; Dentith, M.; Darby, D.; McCarthy, R. (Royal Society of Western Australia, 2004)
The south-west seismic zone (SWSZ) is a northwest-southeast trending belt of intraplate earthquake activity that occurs in the south-western corner of Western Australia, and is one of the most seismically active areas in Australia. Since the SWSZ lies as close as ~150 km from the ~1.4 million population of the Perth region, it poses a distinct seismic hazard. Earthquake activity recorded by Geoscience Australia over the past three decades suggests that the SWSZ could be deforming by 0.5-5 mmy-1. However, little is currently known about the magnitude and orientation of this deformation, and whether there is any associated surface expression. Previous geodetic studies of the SWSZ that used both terrestrial and Global Positioning System (GPS) techniques are inconclusive, due mainly to the imprecision of the technologies used in relation to the likely small amount of any surface deformation. Therefore, a new 48-point GPS-geodetic monitoring network has been established across the SWSZ to attempt to detect surface deformation, for which epoch-one episodic GPS-geodetic measurements were made in May 2002. This paper briefly reviews previous attempts to geodetically measure surface deformation across the SWSZ, summarises the scientific rationale for the new project, describes the network design and observations used, results of the May 2002 campaign (epoch-one) and discusses future work, including issues pertaining to the likely amount of surface deformation that can be detected.